From Stigma to Rights: Restructuring Mental Healthcare in India Through Legislative Reform - Vibha Bose (Journal of Psychology and Social Sciences, 2026)
Mental health has emerged as one of the most pressing public health concerns of the twenty-first century. Despite increasing awareness, stigma, discrimination, and limited accessibility continue to prevent individuals from seeking timely support. Historically, mental illness was viewed predominantly through a medical model that focused on symptom reduction and institutional care. Contemporary perspectives, however, recognize mental health as a fundamental human right requiring dignity, autonomy, equality, and access to quality services. This paper explores the transition of mental healthcare in India from stigma and exclusion to a rights-based approach, with special emphasis on the Mental Healthcare Act, 2017. The paper examines different forms of stigma and their influence on help-seeking behavior. It discusses the major provisions of the Mental Healthcare Act, 2017, including rights related to treatment, confidentiality, informed consent, community living, advance directives, and protection from inhuman treatment. Further, it highlights national and international initiatives and analyses challenges in implementation. Finally, it emphasizes the role of families, educational institutions, workplaces, communities, and mental health professionals in promoting awareness and safeguarding rights. The paper argues that mental healthcare should be understood not merely as treatment of illness but as an issue of dignity, social justice, and human rights requiring collaborative and policy-based interventions.